LANGUAGE AND ARTIFICIAL INTELLIGENCE: NEW HORIZONS - Mohammad Danish Mahmood (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
The rapid development of artificial intelligence (AI) is reshaping our relationship with language in unprecedented ways. From real-time translation tools and conversational agents to AI-generated literature and voice synthesis, language technologies are not only facilitating communication but redefining it. This paper explores the dynamic interplay between language and AI, emphasizing both the transformative potential and the risks posed to linguistic diversity, cultural identity, and communicative authenticity. Through an interdisciplinary lens that draws from linguistics, computer science, and sociocultural theory, this theoretical study analyzes the new horizons opened by AI, with a special focus on English language teaching in Uzbekistan and the responsibility required to ensure these advances align with human values.